PERANAN GURU AKIDAH AKHLAK TERHADAP PEMBENTUKAN AKHLAK PESERTA DIDIK DI MADRASAH ALIYAH DDI AT-TAUFIQ PADAELO KABUPATEN BARRU - Syaifin, Riyo Asmin (JURNAL AL-QAYYIMAH, 2022)
This study aims to find out: about the role of Aqidah Akhlak teachers of students, methods of moral formation and also to find out the supporting and inhibiting factors in the formation of students' morals at MA DDI Attaufiq Padaelo, Barru Regency. The type of research used is descriptive research with a qualitative approach. It is used to describe and present real data and facts about the cooperation of teachers and parents in fostering the morals of students at MA DDI Attaufiq Padaelo, Barru Regency. Methods of data collection using observation, interviews, and documentation. The data analysis technique used is through stages, namely: word reduction, data presentation, and drawing conclusions. The results of this study indicate: 1) The role of the Aqidah Akhlak Teacher on the moral formation of students at MA DDI Attaufiq Padaelo, Barru Regency by guiding students and exemplifying good morals to students so that they can be disciplined, responsible and have good morals and there are activities religion in schools so that students can easily have good morals and good manners to teachers, friends and in their home environment. 2) The method of forming the character of students is developed through exemplary methods. This shows that there is a need for morals to be fostered, and this guidance has resulted in the formation of Muslim individuals with noble character, obedient to Allah and His Messenger, respect for parents, compassion for fellow creatures of Allah. On the other hand, if the child's morals are not developed, problems will arise such as naughty children who always disturb the community and others. 3) The supporting factors in the formation of morality are the cooperation of the family, educators/teachers, and the community. And the inhibiting factors are the lack of religious educationÂ n the family and the attention of parents, and the lack of awareness of the students themselves